HIF-1α relevance in necrosis of mycobacterium avium-induced granulomas - Cardoso, Marcos Levi dos Santos (2015)
The establishment of mycobacterial infection is characterized by the formation of granulomas, which are well-organized aggregates of immune cells, namely infected macrophages. The granuloma main function is to constrain and prevent dissemination of the mycobacteria, while concentrating the immune response to a limited area. In some cases these lesions can grow progressively into large granulomas which can undergo central necrosis leading to their caseation. However, the mechanism underlying this type of pathology is still poorly understood. It has been reported that reduced vascularization of granulomas may be one essential mechanism for caseation and some studies have demonstrated severely hypoxic regions at the center of the granuloma. Under hypoxic conditions the immune cells need to adapt to low oxygen conditions in order to remain functionally active. Thus, the hypoxia-inducible factor – 1 alpha (HIF-1α) has emerged as a master regulator of the hypoxia adaptation system, mediating a wide range of physiological and cellular mechanisms. The Appelberg group has developed a granuloma necrosis model that mimics the human pathology of Mycobacterium tuberculosis, using C57BL/6 mice intravenously infected with a low dose of a highly virulent strain of Mycobacterium avium (ATCC 25291). Such mice develop granulomas that, at 4 months of infection, exhibit central necrosis. To determine the relevance of HIF-1α during M. avium infection we used a mouse strain deleted of HIF-1α under the Cre-lox system in the myeloid cell lineage. The results obtained indicate that HIF-1α deficient mice are more susceptible to the infection and that the onset of necrotic granulomas is faster.